2014
DOI: 10.1021/cn4001928
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of All Forms of Biopterin and Neopterin in Cerebrospinal Fluid

Abstract: In humans, genetic defects of the synthesis or regeneration of tetrahydrobiopterin (BH4), an essential cofactor in hydroxylation reactions, are associated with severe neurological disorders. The diagnosis of these conditions relies on the determination of BH4, dihydrobiopterin (BH2), and dihydroneopterin (NH2) in cerebrospinal fluid (CSF). As MS/MS is less sensitive than fluorescence detection (FD) for this purpose, the most widely used method since 1980 involves two HPLC runs including two differential off-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…Besides, more recently, some authors compared the two proposed chemical oxidation procedures iodine vs. M n O 2 , and they concluded that the oxidation with iodine results in the most accurate determination of N and B in CSF [25]. However, it is now well established that chemical oxidation methods are to underestimate amounts of reduced forms of N and B [9,15].…”
Section: Hplc-fd Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, more recently, some authors compared the two proposed chemical oxidation procedures iodine vs. M n O 2 , and they concluded that the oxidation with iodine results in the most accurate determination of N and B in CSF [25]. However, it is now well established that chemical oxidation methods are to underestimate amounts of reduced forms of N and B [9,15].…”
Section: Hplc-fd Methodsmentioning
confidence: 99%
“…Recently, the effects of pH on the separation and the electro-oxidation of the targeted pterins have been extensively studied [9]. The authors observed that high oxidation yields (≥50%) of BH2 and NH2 can be obtained irrespective of the pH range between pH 3 and pH 8.…”
Section: Hplc-ecd-fd Methodsmentioning
confidence: 99%
See 3 more Smart Citations